Financial aspects of Public-Private Partnership - Livijo Sajko (Central European Public Administration Review)
The growth of public requests is evident in the case of Croatia, but also present in every European country, with the government’s lack of ability to secure sufficient financial income. The look for additional sources of  financing, in order to build public infrastructure, is directed therefore more and more to the private financing capital and to public-private partnerships. Together with such trends, one of the main questions that arise is, whether the employment of private capital in PPP-projects is valid from the economy point of view? If the overall project costs in the PPP-model are lower than the one in the traditional public sector model, calculated with the method of a Public Sector Comparator, the decision can be made to employ private capital in PPP-projects, which is valid from the economy point of view.